Species Composition of Macrofungi in Various Ecosystem in Badung Regency, Bali - Ni Nyoman Sri Kamala Dewi; Ni Made Gari; Luh Putu Eswaryanti Kusuma Yuni; I Made Saka Wijaya (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
Badung Regency is one of the administrative regions located in Bali Province with diverse ecosystems due to high topographic variations. This topographic heterogeneity affects the region's biodiversity, including the diversity of macrofungi. Macrofungi possess distinctive morphological features and potential uses, however, data regarding their diversity in this region remain insufficient. This research aims to assess the species diversity of macrofungi across five ecosystem types (karst, mangrove, lowland, riparian, and highland ecosystems) in Badung Regency, Bali. The research was conducted from January to May 2025 using the belt transect method, with transect placement by purposive sampling. The results revealed that the composition of macrofungi species in Badung regency comprised of 70 species, categorized in 43 genera and 26 families. Polyporaceae is the family with the highest number of species (18 species) which dominated by genus Trametes (eight species). The highland ecosystem in Jempanang recorded the highest species richness (39 species) and the highest diversity index (H'=3.00). On the contrary, the karst ecosystem in Ungasan exhibited the lowest species richness (three species) and diversity index (H’=0.60). The highest genus similarity index was observed between the lowland and riparian ecosystems (SI=59.26%). Conversely, the lowest was between karst and mangrove ecosystems (SI=0.00%). Environmental factors such as air temperature, air humidity, soil pH, soil temperature, soil moisture, and the presence of organic substrates are related to the occurrence and distribution of macrofungi across the research sites.